Cytogenetic analysis reveals existence of swamp buffalo population in Meghalaya - SINGH, KARAN VEER; VERMA, UMA KANT; ARORA, MANISHA; KATARIA, R S; NIRANJAN, SAKET (The Indian Journal of Animal Sciences, 2020)
The present study aimed at assessing the status of the Meghalaya buffalo population from North-East India employing cytogenetic studies. So far buffaloes of the northeastern states of India have been studied except for Tripura and Meghalaya and are generally considered to be of swamp type based on their phenotypic resemblance to swamp type buffaloes. A pilot survey was conducted in the Indian State of Meghalaya for collection of morphometric data from adult animals. The Meghalaya buffaloes investigated cytogenetically possessed a somatic chromosome count of 2N=48, identical to that of typical swamp buffalo, 23 pairs of autosomes and a pair of sex chromosomes. The distinctive karyotypic feature of swamp buffalo observed was due to the distinct size of the fourth pair of metacentric chromosome. No morphological or chromosomal abnormality was observed in any of the populations. This is the first confirmed documentation of existence of pure swamp type buffaloes in Meghalaya state of India.